Classification of patients at risk for chronic kidney disease by use of eGFR and albuminuria - Jelena Seferović; Višnja Ležaić (Биомедицинска истраживања, 2015)
Introduction: Screening for chronic kidney disease (CKD) has been advisedin high-risk populations. However, data on the prevalence of early asymptomaticstages vary and depend on the definition of CKD. In the present studysubjects at risk for CKD (patients with diabetes mellitus type 2-DM2, withhypertension and older than 60 years without diabetes and hypertension)were classified in categories defined by eGFR and albuminuria staging system. Methods: After regular check-up in primary health center, 285 consecutivepatients at risk for CKD, were selected: 75 patients with well-controlled DM2without hypertension, 130 with hypertension and 80 subjects older than 60years without diabetes or hypertension. Screening included a questionnaire,blood pressure measurement, single albuminuria determined by immunonephelometry,and eGFR estimation using MDRD. Results: Six DM2 patients, 15 withe hyprtension and 12 elderly had eGFR<60(assessed in ml/min/1.73m2) with optimal albuminuria. High albuminuriawas observed in one DM2 and four hypertensive patients, and 28 elderly.When eGFR and albuminuria staging system for predicting risk for majorCKD outcomes was used, 41.2% of the elderly were classified in the moderateand 8.8% in the high risk group, for DM2 patients these percentages were9.3% and 0%, and for hypertensive patients 16.9% and 4.7%, respectively. Conclusion: The majority of examined patients did not have CKD, and in allthree groups most individuals with reduced eGFR did not have albuminuria>30mg/g. Using the classification of CKD based on eGFR and albuminuria, it was found that elderly patients had the highest risk for a CKD outcome.
Keywords: patients at risk for CKD; eGFR; albuminuria; CKD categories